Modelling microlayer formation in boiling sodium - Giustini,G; Kim,H; I,Issa R; J,Bluck M (Fluids, 2020)
During boiling at a solid surface, it is often the case that a liquid layer of a few microns of thickness (’microlayer’) is formed beneath a bubble growing on the heated surface. Microlayers have been observed forming beneath bubbles in various transparent fluids, such as water and refrigerants, subsequently depleting due to evaporation, thus contributing significantly to bubble growth and possibly generating the majority of vapor in a bubble. On the other hand, boiling of opaque fluids, such as liquid metals, is not amenable to optical observations, and microlayers have not yet been observed in liquid metals. Among that class of fluids is sodium, suitable as a coolant for nuclear reactors and as the working fluid in phase-change solar power receivers. In order to support these applications, it is necessary to understand the boiling behavior of sodium and identify the parameters that might influence microlayer formation during boiling of this important fluid. This paper presents simulations of the hydrodynamics of sodium vapor bubble growth at a surface. An interface capturing flow solver has been implemented in the OpenFOAM code and used to predict the behavior of a sodium vapor bubble near a solid surface in typical boiling conditions. The methodology has been validated using recently reported direct experimental observations of microlayer formation in water and then applied to sodium boiling cases. Simulations indicate that microlayers are formed in sodium in a similar fashion to water. Comparison of simulation results with an extant algebraic model of microlayer formation showed good agreement, which increases confidence in the current predictions of microlayer formation. Typical values of microlayer thickness thus computed indicate that the microlayer is likely to play an important role during bubble growth in sodium.